In Vivo Selection of Rifamycin-Resistant Clostridium difficile during Rifaximin Therapy - Carman, Robert J. (American Society for Microbiology, 2012)
We report the selection of Clostridium difficile resistant to the rifamycin class of antibiotics in a patient within 32 h of receiving rifaximin for the treatment of recurrent C. difficile diarrhea. Resistance was associated with single nucleotide substitutions within rpoB.